Merging taxonomy to systematics: A holistic approach to understanding the Poecilimon zonatus group (Orthoptera, Phaneropterinae) - Onur Uluar; Dragan P. Chobanov; Battal Çıplak (Arthropod Systematics & Phylogeny)
A taxonomical practice without integration of systematics remains incomplete or produces incorrect definitions. To address this, we linked the taxonomy of the Poecilimon zonatus group to its systematics by examining its phylogeny and phylogeography. We used both mitochondrial and nuclear genes representing all species except P. varicornis. The mitochondrial matrix was subjected to phylogenetic analyses and species delimitation tests while phylogenetic signals in the nuclear data were assessed via haplotype network. Species delimitation tests suggested 12–16 species and the genetically divergent lineages were examined for phenotypic disparity. The results led to the following conclusions. (i) after the nomenclatural changes made here, P. zonatus group consists of 13 species, two of which are polytypic; P. salmani Sevgili syn. nov. is synonymized with P. ciplaki; the subspecies P. ciplaki denizliensis Kaya and P. zonatus datca Sevgili, Sirin, Heller & Lemonnier-Darcemont are elevated to species level as P. denizliensis Kaya stat. nov. and P. datca Sevgili, Sirin, Heller & Lemonnier-Darcemont stat. nov., respectively; P. boncukdagensis sp. nov., P. parazonatus sp. nov. and P. anisozonatus sp. nov., are described as new species, and P. datca montana subsp. nov. and P. denizliensis kizildagi subsp. nov. as new subspecies, (ii) the common ancestor of species corresponds to Mid Pleistocene Transition, suggesting the major climatic turnovers as the main evolutionary driver, (iii) the isolated relict ancestors on highlands evolved under similar selection pressures leading to a conserved phenotype, consequently, to limited morphological divergence despite their genetic differences; (iv) although morphological diagnosability is poor, each species meets the criteria of several species concepts.